Keabsahan Perkawinan Beda Agama Ditinjau Dari Undang-Undang Perkawinan dan Hukum Islam - Airis Aslami; Djanuardi Djanuardi; Fatmi Utarie Nasution (CV. Ulil Albab Corp, 2023)
The legal system currently in force in Indonesia prohibits the practice of interfaith marriages. The Constitutional Court has twice rejected requests for judicial review regarding interfaith marriages; the Indonesian Ulema Council also firmly stated that interfaith marriages are considered haram and illegitimate. However, in its practice, a lot of interfaith couples are able to get married through the assistance of an institution called Indonesian Conference on Religion and Peace (ICRP). Thus, this research aims to examine and determine the legality of interfaith marriages. This research uses a normative juridical approach with an analytical descriptive method. The results of this research show that the Marriage Law views interfaith marriages as illegitimate even though they have been registered at the Civil Registry Office and have obtained an Excerpt of Marriage Certificate, while the Islamic Law views interfaith marriages as haram and illegitimate.